Prevalence of abnormal Pap smears in a consecutive and previously unscreened population in Romania. Issue 2 (17th October 2013) - Stolnicu, Simona; Musca, Simona; Micu, Dorian; Micu, Luminita; Moldovan, Cosmin; Puscasiu, Lucian
Abstract: Objective: To determine the prevalence of abnormal cervical smears in a previously unscreened and asymptomatic population in Romania and to compare the data with those from other countries in Europe. Methods: In a retrospective study, data were reviewed from smears obtained from women in Romania who had been referred to the gynecologist between January 2006 and December 2011. The smears were collected through 3 regional opportunistic programs of cervical screening and were classified according to the Bethesda system. Results: During the study period, 50 536 smear tests were carried out. Of these, 100 smears (0.2%) were unsatisfactory and excluded from the study. Among the remaining 50 436 smears, 2965 patients (5.9%) had abnormal epithelial changes. Most of the abnormal smears were represented by atypical squamous cells of undetermined significance (2.6% of all smears). The data confirmed that there is a high prevalence of high‐grade intraepithelial squamous‐type lesions (0.9% of all smears) in Romania, and of abnormal smears in women younger than 25 years of age (14.0% of all abnormal smears). Conclusion: The data show that there is a high prevalence of epithelial abnormalities among cervical smears in Romania compared with other European countries that run a national screening program.